Development of fish-based breakfast cereal using stuffing and extrusion methods / Norlelawati Arifin - Arifin, Norlelawati (2006)
This work was carried out to develop a fish based breakfast cereal using a single screw extruder with the substitution of cocoyam powder to tapioca starch. There were two types of fish used: Sin Croaker (or gelama) and Shortfin Scad (or selayang). The extruder was designed by ATO, Wageningen and manufactured by Safeworld Enterprise, Klang. The breakfast cereal, which is of salty and fishy taste, was developed to have a texture and shape that is similar to that of normal breakfast cereal in the market. Physicochemical analysis of the starches and fishes such as composition analysis, swelling power, water solubility, amylose content and pasting characteristic were done. It was found that sin croaker had higher amount of protein compared to shortfin scad, in comparison, it was found that the result for fat content was higher for shortfin scad. In addition, the protein content and amylose content of cocoyam powder were found to be significantly higher than that of the tapioca starch even though the former possesses significantly lower moisture content, swelling power and water solubility than tapioca starch. There was no significant difference however, for the fat content even though cocoyam powder had slightly higher fat content compared to tapioca starch. The breakfast cereal was produced using the sausage production method to determine the acceptability of breakfast cereal. 30%, 40% and 50% of sin croaker along with 0%, 20%, 30% and 50% of cocoyam powder in substitution for tapioca starch formulations were processed for this product. Results from the study indicate that a higher score was obtained when 30% and 40% of fish were used in comparison to 50% of fish. In determining the linear expansion, hardness and colour of the product, it was found that the linear expansion decreased as the percentage of cocoyam powder was increased. This also resulted in the hardness of the product to be increased as well as the colour of the product becoming darker.